1982
DOI: 10.1111/j.1432-1033.1982.tb06575.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐ionic Adsorptive Immobilization of Proteins to Palmityl‐Substituted Sepharose 4B

Abstract: 1. Palmityl-substituted Sepharose 4B prepared by the glycidyl ether method of S. Hjerten et al. [ J . Chromutogr. (1974) 101, 281 -2881 has been used as a non-ionic matrix for protein adsorption. A number of proteins, some of which are catalytically active, may be immobilized on this adsorbent in the form of suspension or column.2. Of the proteins examined, bovine serum albumin, hemoglobin, myoglobin, lysozyme, glutamate dehydrogenase, and P-galactosidase were immobilized on the adsorbent irrespective of NaC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…Moreover, the support was found to be reusable after each run of continuous operation, through washing with organic solvents such as toluene or dioxane which eliminate adsorptive interactions between the enzyme and support thereby permitting the dissociation of the enzyme and preparing the support for re-loading by new enzyme. As reported earlier [28][29][30] relatively long alkyl chains (e.g. C18) on the surface of porous silica used in this study, ensure efficient hydrophobic interactions to take place, making the adsorption process virtually irreversible.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Moreover, the support was found to be reusable after each run of continuous operation, through washing with organic solvents such as toluene or dioxane which eliminate adsorptive interactions between the enzyme and support thereby permitting the dissociation of the enzyme and preparing the support for re-loading by new enzyme. As reported earlier [28][29][30] relatively long alkyl chains (e.g. C18) on the surface of porous silica used in this study, ensure efficient hydrophobic interactions to take place, making the adsorption process virtually irreversible.…”
Section: Resultssupporting
confidence: 57%
“…These kinds of strong associations are necessary to retain catalytic activity in continuous operations for the required length of time in optical bio-analysis of the carbaryl. Although warnings were made on the use of long alkyl chains for protein adsorption purposes, due to increasing the risk of denaturation 31,32 results presented here and during the last decades 28,29,33 clearly demonstrate that such process of adsorption is mild and functional properties of a protein are preserved upon adsorption and the product of adsorption is stable enough in continuous transformations or bioanalytical applications (Fig. 6).…”
Section: Resultsmentioning
confidence: 66%
“…This enzyme which showed good affinities for binding to alkyl-substituted adsorbents was found to respond to all positive and negative allosteric modifiers tested, with comparable rates, in free and immobilized forms (Nemat-Gorgani and Karimian, 1982;1983;1984;Nemat-Gorgani et al, 1985). This observation suggested the possibility for immobilizing the enzyme in an allosterically-activated conformation and for design strategies regarding tailor-made enzyme carriers.…”
Section: Disscusionmentioning
confidence: 73%
“…Our own previous studies involving use of hydrophobic supports indicated the possibility of protein adsorption with retention of native properties (NematGorgani and Karimian, 1982;1983;1984;NematGorgani et al, 1985). In such studies, bovine liver glutamate dehydrogenase was used as a model allosteric protein and the immobilized preparation was found to retain its response to all of the relevant allosteric modifiers tested, including L-leucine, in addition to retaining its usual catalytic activities.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation